TELAH ORBIT SATELIT LAPAN-TUBSAT - Nizam Ahmad; Thomas Djamaluddin (Jurnal Sains Dirgantara, 2007)
The study of orbit characteristics of LAPAN-TUBSAT can be done by using some microsatellites which identical in the case of mission and its orbit. This knowledge is usefull to reduce the failure of mission. This characteristics can be seen from the change of orbital elements caused by perturbation forces. LAPAN-TUBSAT is placed in Low Earth Orbit (LEO) at altitude about 630 km which has orbit near polar (i≈98˚). At this altitude, the perturbations come from non-gravitation force such as atmospheric drag and gravitation force from earth oblatness. From the simulation can be predicted that in the early years of its operation, the variation in altitude and semi major axis is relatively small. The means that this satellite could have the life time more than 50 years. The effect of earth oblatness will cause the regression of the nodes of about 1˚/day and the rotation of the line of apsides of about -3˚/day. These changes are not too critical for near polar orbit which means that satellite keeps conducted the mission goal such as satellite imaging.